Analisis Deskriptif Tari Pabbitte Passapu Kajang Kabupaten Bulukumba (Salah Satu Bentuk Pendokumentasi Tari) - Rahma M; Asia Ramli; Muh Kurniawan (Seminar Nasional LP2M UNM, 2022)
Abstract. This study aims to record the Pabitte Passapu dance descriptively, namely by providing a description of the dance in accordance with the actual conditions or in other words according to the original movement with the aim of documenting dance as a form of preservation of traditional dance with a theoretical approach. Documentation of dance which includes data collection carried out directly in Tanatoa Village by meeting the original perpetrators then conducting interviews and demonstrations as well as recording dances, then processing data by recording in the form of writing detailed descriptions of movements accompanied by photos and floor patterns, as well as dissemination which was carried out by documenting the results of this research in the form of reports and carry out scientific publications at national seminars in the form of proceedings and journals as well as include them in the faculty library so that they are easy to find for students and the general public who want to know data related to the Pabitte Passapu Dance, yes which consists of 12 varieties namely, Akkokoroa, Angngibeng, Appakeha, Appalotteng, Sekko Taji, Paganti, A,pabitte, Tannang ulumanu, A,laga, Angngera Seha' which is equipped with photos and floor patterns. Keyword: Descriptive Analysis, Pabitte Passapu Dance